Ultrasound Therapy: Modulation of Abdominal Fat and Triglyceride Levels in Rats - Isnanniah, Isnanniah; Ibrahim, Rabiat Ohunene (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: This study aimed to investigate the effect of ultrasonic wave exposure with different intensity levels on abdominal circumference and blood triglyceride levels in white rats (Rattus norvegicus) as an experimental model for non-invasive fat reduction therapy. Methodology: This study used an experimental in vivo pretest–posttest control group design involving 12 male Wistar rats. Ultrasonic therapy was administered using a 1 MHz ultrasound therapy device with three intensity modes for 4 minutes daily over 6 days. Abdominal circumference was measured using a measuring tape, while triglyceride levels were analyzed using a portable strip-based digital analyzer. Main Findings: The results showed that ultrasonic wave intensity influenced abdominal circumference and blood triglyceride levels in white rats. Mode 2 intensity produced the greatest reduction in abdominal circumference by 6.50%, while Mode 3 most effectively suppressed the increase in triglyceride levels, with only a 0.02% increase. In contrast, the control group showed significant increases in both abdominal circumference and triglyceride levels. Novelty/Originality of this study: This study provides a novel contribution by systematically comparing different ultrasonic intensity modes on both abdominal circumference and blood triglyceride levels simultaneously. The findings identify optimal intensity parameters for non-invasive lipid regulation therapy and expand current knowledge regarding the biophysical application of ultrasound technology in obesity and triglyceride management.